Pemanfaatan Sistem Informasi Geografis berbasis WebGIS terhadap Pemetaan Fasilitas Kota Pasuruan menggunakan Framework CodeIgniter - Farhah Annisa Jamal Firdaus; Fatwa Ramdani; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Pasuruan City is one of the small cities in East Java province. Pasuruan City has a variety of tourist and culinary attractions, and this city has grown rapidly to have many inns and shopping centers. Not a few tourists come to this city to enjoy tourist attractions and culinary delights, as well as for the people themselves to enjoy all the facilities provided in Pasuruan City. The city is quite up-to-date on its website and all social media with the latest news in Pasuruan City. However, of all the sites and social media, the City of Pasuruan does not yet have a special site for mapping the City of Pasuruan which displays various facilities in the form of a map. Therefore, the author builds a Geographic Information System for Pasuruan City by displaying various facilities in Pasuruan City. The method used in the construction of this system is the method waterfall. The results of this study are a-based geographic information system webGIS that has passed the test with results of 93.07% for admin users, and 83.71% for general public users. It can be concluded that this system can be used properly by the entire community of Pasuruan City.